1978
DOI: 10.1097/00006254-197810000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticoagulants Controlled by the British Comparative Thromboplastin Versus Low-Dose Heparin in Prophylaxis of Deep Vein Thrombosis

Abstract: cases, but that the general risk of such complications to women in the Netherlands is slight when abortion has been performed by early vacuum aspiration.We thank the participants in GVR for their kind co-operation, W Breur for the statistical evaluation, and B L Huidekoper for gathering obstetric data. References'Wright, C S W, Campbell, S, and Beazley, J, Lancet, 1972Lancet, , 1, 1278 Summary and conclusions The British comparative thromboplastin (BCT) was used to monitor the effectiveness of oral anticoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 1 publication
0
36
0
Order By: Relevance
“…191,192 The risk of clinically im-portant bleeding at this intensity is modest. A very low fixed dose of warfarin (1 mg daily) prevented subclavian vein thrombosis in patients with malignancy who had indwelling catheters.…”
Section: Prevention Of Venous Thromboembolismmentioning
confidence: 99%
“…191,192 The risk of clinically im-portant bleeding at this intensity is modest. A very low fixed dose of warfarin (1 mg daily) prevented subclavian vein thrombosis in patients with malignancy who had indwelling catheters.…”
Section: Prevention Of Venous Thromboembolismmentioning
confidence: 99%
“…Such comparisons need to be interpreted more cautiously than direct comparisons ( Figure 13) because there is some potential for bias as patients in the trials had different reasons for being at risk of venous thrombosis. Fifteen trials 71,[74][75][76][77][78][79][80][81][82][83][84][85][86][87] had compared an oral anticoagulant regimen versus control, with nine [74][75][76][77][78][79][80][81][82] assessing oral anticoagulant as monotherapy and six 71,[83][84][85][86][87] as adjunctive therapy. Overall, the reduction in DVT appeared similar for moderate and lowintensity regimens, but too few patients had been assessed in trials of very low-intensity regimens for conclusions to be drawn.…”
Section: Effects Of Different Intensities Of Oral Anticoagulationmentioning
confidence: 99%
“…The purpose of this study was to determine if a "lower intensity anticoagulation" (INR between 2.0 and 2.3) compared to "moderate intensity anticoagulation" (INR between 2.5 and 4.1) would diminish the bleeding risk without reducing effectiveness for treatment of deep vein thrombosis (DVT). Other studies, done with the same purpose, showed a reduction in bleeding events while maintaining effectiveness for thrombosis prevention and treatment and systemic embolism in tissue heart valves and atrial fibrillation with less intense anticoagulation [13][14][15][16]. One of the earlier studies even showed effectiveness of anticoagulant therapy at range of INR between 1.6 and 2.5 for the treatment of acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 92%